Opinions of healthcare students on organ and tissue donation for transplantation - Danton Matheus de Souza; Vivian Costa Souza; Winnie Naomi Matsui; Rafael Rodrigo da Silva Pimentel; Marcelo José dos Santos (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the opinions of healthcare students on organ and tissue donation for transplantation. Methods: qualitative document analysis study, using the records of a database and analyzing data from two perspectives: 1) Lexical analysis, with the IRAMUTEQ software, and 2) Thematic content analysis. Results: from the analysis, 3 main categories were generated: 1) Organ and tissue donation as an act of love for others and an opportunity of a new beginning; 2) Clarification and awareness on organ and tissue donation; and 3) Importance of communicating the family and promoting organ and tissue donation. Final Considerations: despite being in favor of donation, students also recognize the presence of social taboos; the discussion in the family nucleus, promoting the theme and raising awareness in society are considered important. Additionally, the education of students is one of the possibilities of intervention for the issue.